SUSTAINABLE DEVELOPMENT: IMPLEMENTASI GREEN ACCOUNTING DAN MATERIAL FLOW COST ACCOUNTING (STUDI KASUS PERUSAHAAN CONSUMER NON-CYCLICALS TAHUN 2021-2023) - Putri Elvina Clarissa Dewi; Nur Isna Inayati; Ani Kusbandiyah; Tiara Pandansari4 (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the contribution of Green Accounting and Material Flow Cost Accounting (MFCA) to the achievement of sustainable development in consumer non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The background of this study stems from the increasing pressure to integrate environmental aspects into business strategies, both as a form of social responsibility and as an effort to maintain the company's legitimacy in the eyes of the public. This research employs a quantitative approach with a sample of 61 companies and a total of 183 observational data points. The testing was conducted using panel data regression analysis with the Random Effect Model (REM). The classical assumption test results indicated no multicollinearity, but heteroscedasticity was found; therefore, Robust Standard Errors were applied in the data processing. The findings reveal that Green Accounting does not have a significant effect on sustainable development, whereas MFCA has a positive and significant influence. These results suggest that cost efficiency through the management of material flows can drive a company’s sustainability achievements. On the other hand, the suboptimal implementation of Green Accounting in strategic decision-making processes hinders its contribution to sustainability. This study provides important implications for companies and policymakers to strengthen the implementation of integrated, measurable, and goal-aligned environmental accounting practices in support of sustainable development.